Motivasi Enterpreneurship dalam Meningkatan Lifeskill Peserta Didik di SD NU Insan Cendekia Kediri - Naim, Ainul; Mahmudah, Siti (Jurnal Penelitian, 2018)
This study aims to determine the role of motivation given by educators in terms of entrepreneurship which will then increase the lifeskills in learners on SDNU Insan Cendekia Ngadiluwih Kediri.This research uses qualitative research method. Research strategy using phenomenological approach. This approach is perceived to understand the meaning of human events and interactions in their particular situations. Researchers take focus in grade 3 and 4 as many as 4 classes. And data collection techniques that researchers take ie from the method of interviewing and documentation. The result of the research concludes that, (1) Prophet Muhammad has a strategy in doing entrepreneurship activities in the form of honesty, maintaining trust, confidence, spirit, business that is really clean, ethical, prospect, diligent, persistent, independent, never give up, take a risk, and have egalitarian personality, (2) On applying entrepreneurship in SDNU Insan Cendekia done by learners and parents, can not be separated from educators who provide an entrepreneurship motivation. From the application of entrepreneurship, it will increase the lifeskills contained in the learner that includes personal skills and social life skills, and (3) Along with held entrepreneurship in learners. Apparently there are several advantages and disadvantages of the application of entrepreneurship. This is because this activity is still done first in this school. Then the need for an evaluation so that the future can be improved again.